DEPRESSION AND QUALITY OF LIFE IN HYPERTENSIVE ADULTS - Maria de Fátima Mantovani; Juliana Perez Arthur; Ângela Taís Mattei; Carina Bortolato-Major; Elis Martins Ulbrich; Luciana Puchalski Kalinke (Universidade Federal do Paraná, 2017)
The present study aimed to investigate the relationship between depression and quality of life in hypertensive adults. Quantitative study with cross-sectional design, with 387 adults with hypertension, conducted in 2014-2015, in 18 Basic Health Units (UBS) in the city of Curitiba, State of Paraná. The tools used to assess quality of life and depression were, respectively, the Medical Outcomes Study 36-Item Short Form Health Survey and Beck Inventory. A significant correlation was found between the worst scores of quality of life and the presence of depression, with great differences between the means in the domains emotional aspects (Confidence Interval = 95%: 26.72% - 42.08%) and mental health (Confidence Interval = 95%: 20.21% - 28.73%). Knowledge of this relationship can help nurses in the planning of care for individuals with hypertension, in the improvement of depressive symptoms and quality of life.